2020
DOI: 10.13181/mji.oa.204008
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy for breast cancer using methylene blue: a new anatomical landmark involving intercostobrachial and medial pectoral nodes

Abstract: BACKGROUND Sentinel lymph node biopsy (SLNB) using blue dye is becoming popular in Indonesia given that knowledge on new anatomical landmarks involving intercostobrachial and medial pectoral nodes have replaced the need for radioisotope tracers. This study aimed to evaluate the utility of the proposed landmark involving intercostobrachial and medial pectoral nodes to determine axillary lymph node status during SLNB. METHODS A prospective study was conducted involving 55 patients with early-stage breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…without metastatic lymph nodes (cN0), 70-80% of these patients have pathologically cancer cell-free lymph nodes (pN0), increasing the risk of unnecessary procedures such as arm lymphedema, axillary sensory impairment, and shoulder adduction deficits. [28][29][30][31][32] This study found that the accuracy of SNLB compared to the histological examination from the axillary lymph node dissection showed a sensitivity of 82.8% and a specificity of 88%. This value is slightly different for patients who have had different types of biopsies.…”
mentioning
confidence: 69%
“…without metastatic lymph nodes (cN0), 70-80% of these patients have pathologically cancer cell-free lymph nodes (pN0), increasing the risk of unnecessary procedures such as arm lymphedema, axillary sensory impairment, and shoulder adduction deficits. [28][29][30][31][32] This study found that the accuracy of SNLB compared to the histological examination from the axillary lymph node dissection showed a sensitivity of 82.8% and a specificity of 88%. This value is slightly different for patients who have had different types of biopsies.…”
mentioning
confidence: 69%
“…In Indonesia, notwithstanding, SLNB for breast malignant growth presently can’t seem to become mainstream thinking about a few variables, including patient qualities (most as of now had the high level stage illness), hazy proposals, and restricted offices for radioisotope use because of significant expenses and inaccessibility in most disease communities ( 9 ). The previously mentioned factors are compounded by the way that Indonesia comprises of numerous islands, making admittance to malignancy focuses considerably more troublesome.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor a (ERa) activation promotes tumorigenesis in different types of cancer, including axillary metastasis breast cancer. The estrogen receptor is a member of the nuclear receptor superfamily and is involved in various developmental and physiological processes ( 5 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation